Warfare, atrocities, and political participation: eastern Africa. Issue 1 (12th January 2018) - Ember, Carol R.; Jones, Eric C.; Skoggard, Ian; Adem, Teferi Abate
Abstract : Purpose: Ember et al. (1992) addressed whether the "democracies rarely fight each other" hypothesis held true in the anthropological record of societies of various sizes and scales around the world. They indeed found that more participatory polities had less internal warfare – or warfare between one society's territorial units (e.g. bands, villages, districts). The purpose of this paper is to examine when political participation would have similar effects in eastern Africa, and whether more participatory polities commit fewer atrocities against each other. Design/methodology/approach: A cross-cultural sample of 46 societies from eastern Africa was used to retest the original Ember et al. (1992) multiple regression model and revised post-hoc models. The team read ethnographies to code for levels of political participation at the local and multilocal levels. Other variables came from previous research including warfare and atrocity variables (Ember et al., 2013 ). Findings: The Ember et al. (1992) model did not replicate in eastern Africa, but analysis with additional variables (degree of formal leadership, presence of state-level organization, and threat of natural disasters that destroy food supplies) suggested that greater local political participation does predict less internal warfare. Also, more participatory polities were less likely to commit atrocities in the course of internal warfare. Originality/value: This study demonstrates regional comparisons are important because they help us evaluate the generalizability of worldwide findings. Additionally, adding atrocities to the study of democracy and warfare is new and suggests reduced atrocities as an additional benefit of political participation.